Comparison of Snail1, ZEB1, E-Cadherin Expression Levels in HPV-Induced Cervical Cancer - FARZANEHPOUR, Mahdieh (Iran J Public Health, 2020)
BACKGROUND: Molecular profiling techniques are the rapid detection of biomarkers in the human papillomavirus (HPV) infected cells. We aimed to measure the expression level of three cell factors including Snail1, ZEB-1, and E-cadherin in cervical cancer (CC), precancerous and healthy samples, simultaneously, to find potential biomarkers. METHODS: The expression level of the mentioned cell factors were investigated in 72 CC patients, precancerous patients, and healthy controls by using Real-Time PCR. RESULTS: The results demonstrated a significant reduction in the expression level of E-cadherin in cancer and precancerous cases than that in healthy cases; whereas the expression level of ZEB-1 and Snail1 were upregulated in cancer and precancerous samples. The receiver operating characteristic (ROC) analyses shows the highest AUC value emerged for Snail1: 1(95% CI: 1-1) in comparing CC and healthy groups with a sensitivity of 100.0 % and specificity of 100.0%. CONCLUSION: The molecular biomarker Snail1 may be helpful to early diagnosis and prognosis of CC in the HPV-infected human populations. Considering the increased expression level of Snail1 in cancer and precancerous tissue compared to healthy tissue as well as the area under the ROC curve, Snail1 can be used for early detection of CC.